In vitro effects of antipsychotics on mitochondrial respiration - Cikánková, Tereza; Fišar, Zdeněk; Bakhouche, Yousra; Ľupták, Matej; Hroudová, Jana (Naunyn-Schmiedeberg's archives of pharmacology, 2019)
Assessment of drug-induced mitochondrial dysfunctions is important in drug development as well as in the understanding of molecular mechanism of therapeutic or adverse effects of drugs. The aim of this study was to investigate the effects of three typical antipsychotics (APs) and seven atypical APs on mitochondrial bioenergetics. The effects of selected APs on citrate synthase, electron transport chain complexes (ETC), and mitochondrial complex I- or complex II-linked respiratory rate were measured using mitochondria isolated from pig brain. Complex I activity was decreased by chlorpromazine, haloperidol, zotepine, aripiprazole, quetiapine, risperidone, and clozapine. Complex II + III was significantly inhibited by zotepine, aripiprazole, quetiapine, and risperidone. Complex IV was inhibited by zotepine, chlorpromazine, and levomepromazine. Mitochondrial respiratory rate was significantly inhibited by all tested APs, except for olanzapine. Typical APs did not exhibit greater efficacy in altering mitochondrial function compared to atypical APs except for complex I inhibition by chlorpromazine and haloperidol. A comparison of the effects of APs on individual respiratory complexes and on the overall mitochondrial respiration has shown that mitochondrial functions may not fully reflect the disruption of complexes of ETC, which indicates AP-induced modulation of other mitochondrial proteins. Due to the complicated processes associated with mitochondrial activity, it is necessary to measure not only the effect of the drug on individual mitochondrial enzymes but also the respiration rate of the mitochondria or a similar complex process. The experimental approach used in the study can be applied to mitochondrial toxicity testing of newly developed drugs.
Keywords: Energy Metabolism; respirační komplex I; techniky in vitro; Swine; Antipsychotic Agents; Animals; Electron Transport Complex I; prasata; Brain; In Vitro Techniques; Mitochondria; Electron Transport Complex II; mitochondrie; respirační komplex II; mozek; zvířata; energetický metabolismus; antipsychotika